2019
DOI: 10.1093/ejo/cjy080
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the palatal shape and arch dimension in subjects with palatally displaced canine

Abstract: Summary Objectives The aim of this study is to analyse the morphological variations of the palate shape and maxillary arch dimension in a group of subjects with unilaterally or bilaterally impacted maxillary canines compared with a control group, using three-dimensional (3D) geometric morphometric. Materials The subject of this study consisted of pre-treatment records of 46 (18 males and 28 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…But previous studies of unilaterally and bilaterally palatally impacted canines denoted no significant palatal vault morphology, and the observed subjects showed no maxillary transverse constriction except for a significant reduction in the intercanine width between the two groups. 39 Our findings of decreased transverse palatal width and shallow palatal height substantiate the findings of Tang et al, who found a decreased palatal vault depth and palatal intermolar area when measured on casts of growing children with PIMC. 40 Our study shed some light on the effects of the transverse dimension of the palatal morphology at various levels of the teeth, such as the CEJ, the alveolar crest, and the mid-root level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…But previous studies of unilaterally and bilaterally palatally impacted canines denoted no significant palatal vault morphology, and the observed subjects showed no maxillary transverse constriction except for a significant reduction in the intercanine width between the two groups. 39 Our findings of decreased transverse palatal width and shallow palatal height substantiate the findings of Tang et al, who found a decreased palatal vault depth and palatal intermolar area when measured on casts of growing children with PIMC. 40 Our study shed some light on the effects of the transverse dimension of the palatal morphology at various levels of the teeth, such as the CEJ, the alveolar crest, and the mid-root level.…”
Section: Discussionsupporting
confidence: 91%
“…But previous studies of unilaterally and bilaterally palatally impacted canines denoted no significant palatal vault morphology, and the observed subjects showed no maxillary transverse constriction except for a significant reduction in the inter-canine width between the two groups. 39…”
Section: Discussionmentioning
confidence: 99%
“…The results of comparing the groups (one and two impacted canines compared with CG) showed no significant difference in palatal shape. However, the width between the canines of t’he impacted groups based on linear measurements was significant compared to the CG subjects [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this advanced methodology has been utilized in dentistry, particularly for orthodontics, to examine shape variations, including the shape of the palate in relation to the skeletal structure [17,18] and tooth positioning [19,20]. There has also been a recent study utilizing this method to analyze tooth morphology in relation to the malocclusion type [21].…”
Section: Introductionmentioning
confidence: 99%